PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN PADA KETERLAMBATAN PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BEI - Pande, Ni Putu Sonia Sindica; Mertha, I Made (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
Any company that went public have an obligation to submit financial statements on time. Long time submission of financial statements may affect the value of companies, because of timeliness in the delivery of financial statements and financial reports are good quality or in accordance with FinancialiAccountingiStandards may encourage investors to invest in the company . This study was to determine the effect of profitability, solvency and size of the company in the late submission of financial statements of companies listed on stock exchanges in 2011-2014 Indonesia multiple linear regression analysis technique used to conduct this study. Collection method used is secondary data source. The results of analysis show that the profitability of a negative effect on the late submission of financial reports, solvency positive influence on the late submission of financial statements, while the company size has no effect on the late submission of financial statements of the company.
Keywords: profitability, solvency, company size, the late submission of financial statements